The impact of AIDS on the Botswana civil service: a case study of the police and prison services - Gossett, Charles W. (2010)
That HIV/AIDS has had an enormous impact on southern Africa in general, and in Botswana in particular, is not in doubt. Numerous studies have documented certain aspects of the problem - high HIV prevalence rates, increasing numbers of orphans and vulnerable children, declining average life expectancy, and a high number of deaths among adults during their most productive years. Scholars have engaged in speculation about the possible impacts that this disease might have on social relationships, economic growth and development, and governance in both the near and the long terms. But these studies are only forecasts of possible futures, not data driven analyses. This study closely examines data available from two agencies in the Botswana civil service, the police and prisons services in an effort to assess, albeit indirectly, any impact that the HIV/AIDS crisis may have had on the workforce. Although the AIDS epidemic in the country as a whole was reflected in the experience of these services, neither agency suffered the devastating effects some feared. - Reproduced.
Keywords: Bureaucracy - Botswana; AIDS - Botswana; Civil service - Botswana; Civil service